Bioenergi från röjningsgallringar - Andersson, Christoffer (2005)
When the Swedish Forestry Act was changed in 1994, brushing of young stands became non mandatory. Since then the annual need for brushing in the country has increased by about 100 000 hectares per year. In later years the price for biomass energy has increased to the same level as pulp wood. The high price on biomass energy and the large areas of stands in the need of brushing has created a new market with its own technical, economical and environmental conditions. There is a development of various techniques to manage the forestry stands with late brushing.